The Tyranny of ‘Best Practices’: Structural Violence and Writing Programs - Roger Thompson (Journal of the Assembly for Expanded Perspectives on Learning, 2018)
“Best practices” serve writing programs most effectively if participants use them as guidelines for inquiry and local adaptation.